Achieving tolerant CO2 electro-reduction catalyst in real water matrix - Won, Da Hye; Shin, Hyeyoung; Chung, Min Wook; Jung, Hyejin; Chae, Keun Hwa; Oh, Hyung-Suk; Hwang, Yun Jeong; Min, Byoung Koun (ELSEVIER, 2019)
In order to achieve practical application of electrochemical CO2 conversion technologies, the development of durable catalyst in real water matrix is essential because the use of catalysts only showing high performance within a well-refined environment cannot guarantee their feasibility in realistic conditions. Here, we report a design strategy for a catalyst, which shows excellent tolerance to deactivation factors, using a carbon-based material under more practical condition implemented by real tap water. Screening analyses on various components in tap water elucidated that the impurity group, which can be deposited on the catalyst surface and impede the active sites, such as copper, zinc, and especially iron are the main factors responsible for deactivation. Based on these findings, the structural modified nitrogen-doped carbon nanotube (denoted as ball mill N-CNT) was adopted as a catalyst design to secure durability. Consequently, the ball mill N-CNT revealed tolerance to the disclosed deactivation factors and showed stable performance during unprecedented long-time of 120 h in tap water media.
Keywords: CARBON-DIOXIDE REDUCTION; DEPENDENT ELECTROCATALYTIC REDUCTION; ELECTROCHEMICAL REDUCTION; EFFICIENT ELECTROREDUCTION; HIGHLY EFFICIENT; HIGH SELECTIVITY; CONVERSION; GRAPHENE; DEACTIVATION; FORMATE